Performance characterization of a vanadium redox flow battery at different operating parameters under a standardized test-bed system. (1st January 2015) - Mohamed, M.R.; Leung, P.K.; Sulaiman, M.H.
Highlights: Performance study of V-RFB under different operating parameters such as. Current densities, temperatures, flow rates, concentrations and material properties. Formation charge predicted using electrochemical calculation of Faraday's constant. Poor performance for imbalance vanadium concentration and supporting electrolyte. High temperatures improved conductivity but excessive generates secondary reaction. Abstract: This paper describes the experimental characterization of a 25 cm 2 laboratory scale vanadium redox flow battery (V-RFB). The unit cell performance with respect to voltage, coulombic and energy efficiencies under different performance parameters (current densities, operating temperatures, flow rates, electrolyte concentrations and material properties of 5 cm × 5 cm electrodes) are presented. The cell exhibits different characteristics under different operating parameters; the highest energy efficiency is recorded at c.a. 82%, operating at 308 K, 60 mA cm −2 and 3 cm 3 s −1 volumetric flow rate for 250 cm 3 electrolytes (each reservoir) of 1.6 mol dm −3 V(III) / V(IV) in 4 mol dm −3 H2 SO4 . Formation charge of the mixture of vanadium species into single electro-active species at positive and negative electrodes are presented. Estimated time for the electro-active species to complete the formation charge using electrochemical calculation of Faraday's constant are presented; a discrepancy of 4.5% is found between the theoretical and experimental data using current density of 80 mA cm −2 .